A Critical Study of Harald Motzki's Methodology in Proving the Authenticity of the Jurisprudential Narrative of Early Meccan Madhhab - Marouane El Habchi (دورية نماء لعلوم الوحى والدراسات الإنسانية, 2025)
This research aims to cover an early period in the history of the development of the Meccan legal school, a period overlooked by the German orientalist Harald Motzki in his work titled The Origins of Islamic Jurisprudence: Meccan Fiqh Before the Classical Schools. The study revisits the era during which the founder of the school 'Abdullàh Ibn ‘Abbas was active, examining his efforts that contributed to the establishment of the Meccan school. After the introduction, the research discusses the reasons behind Motzki's choice of ʿAbd al-Razzaq’s Musannaf as a text to apply his methodology—studying Isnad-cum-Matn. It also outlines the criteria that Motzki relied upon to conclude that Ibn Jurayj’s narrations from ʻAṭāʼ Ibn Abi Rabah and ʻAmr ibn Dīnār are authentic. Subsequently, the study delves into Ibn ‘Abbas’s role in founding the Meccan school by examining his contributions in political assemblies, scholarly circles, his leadership in issuing fatwas, and shaping what could be termed the concept of scholarly authority. Additionally, the research emphasizes the importance of peer testimony in reinforcing Motzki’s conclusions. The study concludes by affirming that covering Ibn ‘Abbas’s period places the researcher at the actual starting point of the Meccan legal school and sheds light on how legal discourse began to take shape during that era.